1997
DOI: 10.1002/jpln.19971600218
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Processes Related to Ammonium Toxicity in Higher Plants

Abstract: Nitrate and ammonium have different effects on many biochemical and physiological processes in plants, and at high concentrations this can lead to markedly different growth responses. Most plant species show reduced growth, smaller leaves and a stunted root system when exposed to high ammonium concentrations, and in severe cases this leads to chlorosis. Although well known, ammonium toxicity is poorly understood and is generally considered to be the result of one or more of the following effects; (i) ammonium‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
308
1
7

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(333 citation statements)
references
References 89 publications
14
308
1
7
Order By: Relevance
“…Although other studies have shown that some species develop toxic symptoms when only NH 4 + nutrition is applied (Gerendás et al, 1997;Lasa et al, 2001), the citrange Carrizo N-NH 4 + plants displayed optimal growth, estimated on the basis of biomass production (Fig. 1A).…”
Section: Development Of the Citrange Carrizo Plants Grown Under The Nmentioning
confidence: 85%
See 2 more Smart Citations
“…Although other studies have shown that some species develop toxic symptoms when only NH 4 + nutrition is applied (Gerendás et al, 1997;Lasa et al, 2001), the citrange Carrizo N-NH 4 + plants displayed optimal growth, estimated on the basis of biomass production (Fig. 1A).…”
Section: Development Of the Citrange Carrizo Plants Grown Under The Nmentioning
confidence: 85%
“…The analysis of PAs in our study has determined that N-NH 4 + treatment induces a faster, stronger Put accumulation at 2 h (data not shown) and at 14 d in the absence of salt. It is commonly accepted that some species develop toxic symptoms when NH 4 + nutrition is applied (Gerendás et al, 1997;Lasa et al, 2001), while a negative effect on plant growth has been observed with this kind of nutrition (Claussen and Lenz, 1999;Walch-Liu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NH4 + is preferentially taken up by Sphagnum (Fritz et al, 2014;Liu et al, 330 2013; Wiedermann et al, 2009) because Sphagnum has a high cation exchange capacity 331 (Bates, 1992;Gunnarsson & Rydin, 2000). In addition, NH4 + has greater toxicity 332 (Gerendás et al, 1997;Krupa, 2003;Stevens et al, 2011). DON concentration in pore water (Fig.…”
Section: Science Of the Total Environment Chiwa Et Al Revised Msmentioning
confidence: 98%
“…(NH4 + ) versus oxidized (NO3 -) N on the N status of the Sphagnum moss and the (Manninen et al, 2011;Sheppard et al, 2014), possibly due to the greater toxicity of 97 NH4 + (Gerendás et al, 1997;Krupa, 2003;Stevens et al, 2011;Limpens and Berendse, 98 2003) coupled to preferential uptake of NH4 + by Sphagnum (Fritz et al, 2014;Liu et al, 99 2013; Wiedermann et al, 2009). For example, Manninen et al (2011) found that NH4 + 100 addition increased shoot N concentration of Sphagnum and decreased photosynthetic 101 variables (Fv/Fm) and shoot dry weight of Sphagnum.…”
mentioning
confidence: 99%